Designing a sportswear strategic marketing plan: a data analytics approach / Mohammad Noorizzuddin Nooh - Nooh, Mohammad Noorizzuddin (2022)
This paper begins by simulating a scenario in which the researcher received funding from venture capital to start a sportswear venture in Malaysia. The goal is to maximise the ROI by the end of the first year. The sportswear industry is a big industry with many renowned players. The researcher uses data analytic techniques to analyse online search trends, categorical search and Geomap patterns. Data analytics assists in segmenting audiences by distinct demographic categories and analysing opinions and trends in each of them. The analysis results are utilised to undertake SWOT analysis, Porter's Five Forces Competitive Models, and assist in developing the company's marketing mix. This paper opens with an industry overview to provide a bird's-eye view. According to industrial data, the sportswear business is large, involving numerous well-known companies. The part on literature review includes literature on brand, online brand, retailers and channel, and online shopping. It provides a thorough background on the studies done in various areas.